2020
DOI: 10.1108/jeee-06-2019-0076
|View full text |Cite
|
Sign up to set email alerts
|

Do country level constructs affect the relation between self-efficacy and fear of failure?

Abstract: Purpose This paper aims to show how country level constructs (investment protection, registration cost and legal protection) moderate the relationship between self-efficacy and fear of failure (FoF). Design/methodology/approach The authors use global entrepreneurship monitor (GEM) data and augment it with country level data for 12 counties from different levels of economic development. The entrepreneurship literature has not yet addressed the micro/macro level influences on FoF to the best of the authors’ kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…When people are less protected, they tend to experience FoF. There is evidence that unfavorable policies like high registration costs and less legal protection increase FoF (Kamal & Daoud, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When people are less protected, they tend to experience FoF. There is evidence that unfavorable policies like high registration costs and less legal protection increase FoF (Kamal & Daoud, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It is an individual motive to avoid success to prevent humiliation as a consequence of failure (Acquah, Nsiah, Antie, & Otoo, 2021;Graham, 2020). Social psychology studies define FoF as a socio-cultural trait that influences attention to rewards in the social environment (Hayton, Cacciotti, Giazitzoglu, Mitchell, & Ainge, 2013;Kamal & Daoud, 2020;Vaillant & Lafuente, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…At the macro level, the impact of fear of failure is greater than that of individual factors (Kamal & Daoud, 2020), and research on the related effects of policy and culture on fear of failure is mainly conducted. From a policy perspective, different countries have varying degrees of friendliness towards entrepreneurial failure in reducing its negative impact on entrepreneurs.…”
Section: Environmental Aspectmentioning
confidence: 99%
“…Hope, self-efficacy, optimism, and resilience are critical factors that make up PsyCap [78,79]. Kamal and Daoud [80] found that self-efficacy is a crucial factor that helps reduce the fear of failure. Similarly, Salisu [81] and Reivich and Shatté [82] found that resilience is a vital resource for entrepreneurs' success in emerging markets.…”
Section: Psychological Capitalmentioning
confidence: 99%